2012
DOI: 10.1007/s10853-012-6387-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure and electronic states in a-Si:H thin films

Abstract: The hydrogenated amorphous silicon (a-Si:H) thin films were prepared by plasma enhanced chemical vapor deposition at various substrate temperatures. This paper examined the relationship between structural evolution and electronic states of the tested thin films. Raman spectroscopy was used to evaluate the structural evolution in amorphous network. Meanwhile, Fourier transform infrared spectroscopy was applied to explore the change of hydrogen in thin films. Results show that the order of network on short and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In this paper, attempts are mainly focused on the relationship between Raman characteristic parameters and structural properties in both as‐deposited and annealed a‐Si 1 − x Ru x thin films. It is demonstrated that the structure of Si‐based amorphous thin films is sensitive to the deposition parameters and the post‐deposition treatment because of the metastability of a‐Si network . In our consideration, the introduced Ru atoms, whose size and eletronegativity are different from Si atoms, would cause distortion of a‐Si network in both as‐deposited and annealed states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, attempts are mainly focused on the relationship between Raman characteristic parameters and structural properties in both as‐deposited and annealed a‐Si 1 − x Ru x thin films. It is demonstrated that the structure of Si‐based amorphous thin films is sensitive to the deposition parameters and the post‐deposition treatment because of the metastability of a‐Si network . In our consideration, the introduced Ru atoms, whose size and eletronegativity are different from Si atoms, would cause distortion of a‐Si network in both as‐deposited and annealed states.…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that the structure of Si-based amorphous thin films is sensitive to the deposition parameters and the post-deposition treatment because of the metastability of a-Si network. [7,8] In our consideration, the introduced Ru atoms, whose size and eletronegativity are different from Si atoms, would cause distortion of a-Si network in both as-deposited and annealed states. This distortion could further degrade the short-range order and medium-range order of a-Si 1 À x Ru x thin films.…”
Section: Introductionmentioning
confidence: 99%